Examining Cretaceous Strata of the Taylor Creek Group in British Columbia : Potential Connection of the Methow and Tyqughton Basins. - Forgette, Michelle M. (My University, 2009)
Cretaceous strata around the Chilcotin Plateau of south-central British Columbia are traditionally described as occupying several distinct basins, including the Nechako, Methow and Tyaughton basins. The original geometric relationships between these basins are difficult to reconstruct due to Eocene and Neogene volcanic cover and the presence of a Tertiary dextral transpressive fault system along the southern margin of the Plateau. Detailed sedimentologic and stratigraphic analysis are being integrated with ongoing thin section petrography, shale geochemistry (REE and isotopes), palynology, macro- and microfossil studies, and detrital zircon analyses in both these formations to test this proposed stratigraphic correlation.
Color poster with text and charts describing research conducted by Michelle Forgette, advised by J. Brian Mahoney.
Keywords: Chilcotin Plateau (B.C.); Stratigraphic correlation--British Columbia; Cretaceous/Tertiary boundary--British Columbia; Geology, Stratigraphic--Cretaceous; Posters